Appropriation, Opting Out, and the Common Good in Public Debates: An Analysis of Christian Ethical Arguments - Dunn, Shannon (Journal of law and religion, 2023)
This article examines anti-mask protests in the United States in the context of the COVID-19 pandemic. Specifically, I look at the cultural (mis)appropriation of slogans by anti-mask protestors, such as "I can’t breathe" and "My body, my choice." Noting that this is at first glance a bit of a puzzling phenomenon, I show that there is a relationship between the anti-mask protest, white Christian grievance politics, and the disintegration of the public sphere. Drawing on the work of Bonnie Honig, I argue that the anti-mask protests represent a mode of opting out of public engagement, hence opting out of the practice of using rational argumentation to explain why things ought to be a certain way, as well as listening to the reasons of others. Insofar as this has become a popular mode of engagement among a significant number of Americans, it needs to be understood in the language of foregoing responsibility for others in US pluralistic democracy. Indeed, further explication of the relationship between responsibility and freedom is absolutely necessary. I maintain that opting out is ethically untenable because of the nature of interdependence with others and the necessity of adhering to the rule of law. An ethic of reciprocity properly grounds an understanding of embodied freedom, resisting the extremes of grievance politics.